Application of the PBL Model with Multimedia in Improving Class IV Social and Science Learning Result at SDN Nglanduk 2 - Salma Pigi Taqiyyah, Anisah; Ambarwati , Rosita; Istikomah , Nur (Universitas Islam Indonesia, 2024)
Teachers still face various challenges in implementing learning in the classroom. Some of them are students who are less active, lack of use of technology, lack of use of concrete objects, and students' social and science learning outcomes that have not yet reached the criteria for achieving learning objectives. The research entitled